Strategies for Increasing Student Participation in English Class Discussions through the Think-Pair-Share Technique - Haryadi, Rofiq Noorman; Eryandi, Eryandi (Journal of Applied Linguistics and English Education, 2024)
Increasing student participation in class discussions is a major challenge in English language teaching. One effective method to enhance student engagement is the Think-Pair-Share (TPS) technique. This study aims to explore strategies for using the TPS technique to increase student participation in English class discussions. The TPS technique consists of three stages: thinking individually, discussing with a partner, and sharing thoughts with the class. Through this approach, students are given the opportunity to think independently before interacting with their partner, which encourages greater confidence in expressing their ideas. Furthermore, by sharing their thoughts with the class, students also learn to listen to and value their peers' viewpoints. This research adopts a qualitative method, using observation and interviews as data collection tools. The results indicate that the application of the TPS technique significantly increases student participation, boosts their confidence in using English, and fosters a more inclusive learning environment. Students who were previously passive in discussions became more active and open in expressing their ideas. Therefore, implementing the TPS technique can be considered an effective strategy to enhance student interaction in English classes, which, in turn, can improve their learning outcomes